Interaction between body sensations and movement practices in the formation of choreographic performance style - Шетеля Наталія; Shetelya Natalia; Черкасов Володимир; Cherkasov Volodymyr (Видавництво «Код», 2025)
Abstract. The article proves that the interaction between bodily sensations and movement exercises forms the basis of choreographic performance style. Physical exercises and conscious movements contribute to the development of dancers, improving their technical skills and emotional expressiveness. This allows not only to perform movements, but also to feel and understand one’s body on a deeper level during dance. Listening to one’s body, asking questions, analyzing and exploring the entire spectrum of movement variations are professional skills that a modern dancer must possess if he wants to achieve professional perfection in the modern choreographic space. Awareness of physical sensations and the process of movement in each moment creates a space where transformation can occur. Through sensitivity to one’s own body, the dancer tunes in to more subtle, deeper levels. Let’s consider a few common self-regulation techniques, such as muscle relaxation and breathing regulation. The ability to control muscle tension and relaxation in the necessary muscle groups during a particular movement is one of the basic elements of modern dance. As a result, the technique under study is transformed from simply learning to relax muscles to learning to consciously use muscle relaxation and tension. A method of creating a new dance language that is not associated with outdated «meaningful» and «ideological» associations, a phenomenology of the body, which can be interpreted as a study of simple body movements and the kinesthetic sensations associated with them. The main theme of the dance will be the presence of the body «here and now», which is rooted in the experience of everyday life. At the same time, the absence of psychological and artistic «events» is compensated by the perception of movement as a physical and motor event. The dancer feels emotions and images of movement, its meaning, quality, forms, texture, that is, a visual and kinetic form. Modern American researchers believe that all forms of movement organization in the creative structure are reflected in movement. Dance is no less rational than conceptual thinking, but each dancer differs in the level of bodily consciousness, which can primarily be perceived using verbal means.

Резюме. У статті доведено, що взаємодія між тілесними відчуттями та руховими вправами становить основу хореографічного виконавського стилю. Фізичні вправи та свідомі рухи сприяють розвитку танцівників, покращуючи їхні технічні навички та емоційну виразність. Це дозволяє не тільки виконувати рухи, але й відчувати та розуміти своє тіло на більш глибокому рівні під час танцю.
Взаємодія тілесних відчуттів та рухових практик у формуванні хореографічного виконавського стилю
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: bodily sensations; movement practices; choreographic performance style